Design Documentation in Education: - Merheb, Rita (2025)
This paper examines how design documentation in higher education can function as a form of cultural preservation within the Gulf region, using the American University of Kuwait (AUK) as a case study. Through a qualitative analysis of seven student-led capstone projects, the research explores how design students act as cultural documentarians, transforming local traditions, oral histories, and vernacular aesthetics into designed artifacts that preserve regional visual culture. Drawing on frameworks from design pedagogy, cultural heritage studies, and practice-based research, the study positions design documentation as both a learning process and a mode of cultural stewardship. Findings reveal that when documentation practices are embedded into the design curriculum, students gain critical research and storytelling skills while contributing to community-driven archives of intangible and tangible heritage. The paper concludes that design education can serve as a living archive, bridging traditional narratives with contemporary design practice, and argues for integrating documentation as a sustained pedagogical strategy in art and design programs across the region.